Sonic and ultrasonic scalers in periodontal treatment: a review - T Arabaci (Journal compilation 2007 Blackwell Munksgaard, 2007)
Periodontal therapy aims at arresting periodontal infection and maintaining a healthy periodontium. The periodic mechanical removal of subgingival microbial biofilms is essential for controlling inflammatory periodontal disease.